2020
DOI: 10.1097/md.0000000000022664
|View full text |Cite
|
Sign up to set email alerts
|

An extensive posterior circulation infarction secondary to primary hyperthyroidism accompanied with superior mesenteric artery syndrome

Abstract: Introduction: Hyperthyroidism-related anterior circulation ischemic events have been well documented; however, posterior circulation infarction is rarely reported, not to mention with superior mesenteric artery syndrome (SMAS), which has never been reported concurrently. We describe, to the best of our knowledge, the first case of hyperthyroidism-related cerebellar infarction accompanied with SMAS. Patient concerns: A 22-year-old women presented with palpitation, postpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The diagnosis is difficult because of the risk of cystic fibrosis enteropathy[ 24 ]. Other rare associations are hyperthyroidism-related sympathetic hyperstimulation, vasculopathy and cerebellar infarction[ 46 ] and diabetic patients with excessive body weight loss and associated ketoacidosis after using sodium-glucose cotransporter 2 inhibitors[ 47 ]. Rare associations with rheumatoid arthritis and rheumatoid cachexia have also been reported[ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is difficult because of the risk of cystic fibrosis enteropathy[ 24 ]. Other rare associations are hyperthyroidism-related sympathetic hyperstimulation, vasculopathy and cerebellar infarction[ 46 ] and diabetic patients with excessive body weight loss and associated ketoacidosis after using sodium-glucose cotransporter 2 inhibitors[ 47 ]. Rare associations with rheumatoid arthritis and rheumatoid cachexia have also been reported[ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that both diabetes and Graves' disease induce wasting among those affected by these disorders, a combination of these diseases can precipitate SMAS. However, there have only been a few studies concerning the incidence of SMAS due to diabetes and Graves' disease ( 8 , 9 ). More importantly, such studies have shown that SMAS usually occurs after a long duration of diabetes.…”
Section: Introductionmentioning
confidence: 99%